Analisis Penataan Perkampungan Kumuh : (Studi pada Kelurahan Oimbo Kecamatan Rasanae Timur Kota Bima) - Bayu Budiansyah (International Forum of Researchers and Lecturers, 2023)
Research objectives: 1) To find out the arrangement of slums through restoration (rehabilitation) in Oimbo Village, Bima City? 2) To find out the arrangement of slums through rejuvenation (revitalization) in Oimbo Village, Bima City? 3) To find out the arrangement of slums through resettlement (relocation) in Oimbo Urban Village, Bima City? This type of research is descriptive qualitative. Data collection techniques are interviews, observation, and documentation. Informants in this study included the Head of Kelurahan and staff/employees and community leaders in Kelurahan Oimbo Kota Bima. Determination of informants in this research the author uses purposive sampling technique. The analysis technique used is descriptive qualitative analysis, which starts from data reduction, data display, and verification and conclusion making. The results of the research are: first, related to the arrangement of slums through restoration (rehabilitation) in Oimbo Village, Bima City, has been carried out well according to the needs of residents. Second, the arrangement of slums through rejuvenation (revitalization) in Oimbo Village, Bima City, has been carried out well according to the needs of the residents. Third, the arrangement of slums through resettlement (relocation) has been carried out well according to the needs of residents.